Immersea: Sistem Monitoring Terpadu Kondisi Air Penunjang Budidaya Rumput Laut Berbasis Internet of Thing dan Artificial Intelligence Secara Real Time - Raihansyah, Muhammad Zaki; Alim, Sufadi; Priyantama, V. Karocelli Leo; Febrianti, Diva Dinanti; Manggala, Yossie Rendy Tegar; Putra, Hamdana (Universitas Batanghari Jambi, 2024)
This research aims to help seaweed farmers optimize seaweed cultivation in Indonesia, by using a tool called Immersea based on the Internet of Things and Artificial Intelligence, farmers can monitor water quality conditions in real-time via smartphone and get additional references for appropriate action. water conditions. The research method used is a combination of descriptive and experimental methods with experiments on a prototype scale. Tests were carried out in seaweed ponds in Jabon District, Sidoarjo. The research results found that sensor readings can be observed on a smartphone application in real-time with a data transmission speed of 30 seconds/data, and data transmission for tool direction control is ±35 seconds/data.